2019
DOI: 10.1002/ijc.32295
|View full text |Cite
|
Sign up to set email alerts
|

Using plasma cell‐free DNA to monitor the chemoradiotherapy course of cervical cancer

Abstract: The liquid biopsy is being integrated into cancer diagnostics and surveillance. However, critical questions still remain, such as how to precisely evaluate cancer mutation burden and interpret the corresponding clinical implications. Herein, we evaluated the role of peripheral blood cell‐free DNA (cfDNA) in characterizing the dynamic mutation alterations of 48 cancer driver genes from cervical cancer patients. We performed targeted deep sequencing on 93 plasma cfDNA from 57 cervical cancer patients and from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…Recent liquid biopsy studies showed that cell-free DNA (cfDNA), which originates from the apoptosis and necrosis of normal and tumor cells may be valuable for monitoring tumor behaviors and treatment responses [ 6 8 ]. The detection of HPV16 and HPV18 DNA or alterations in the cfDNA of patients with CC patients is used as biomarkers for recurrence monitoring [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent liquid biopsy studies showed that cell-free DNA (cfDNA), which originates from the apoptosis and necrosis of normal and tumor cells may be valuable for monitoring tumor behaviors and treatment responses [ 6 8 ]. The detection of HPV16 and HPV18 DNA or alterations in the cfDNA of patients with CC patients is used as biomarkers for recurrence monitoring [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported that tumor size is a prognostic factor used to predict patient progression and outcomes [51]. A Previous study related to AFD demonstrated the effectiveness of AFD in predicting the benefit and response of cervical cancer patients to treatment and the predicted evidence of metastases was better than tumor size [27]. AFD performed in our study was independent of the tumor size, patients with high AFD had worse progression compared to patients with low AFD values.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, dVAF has also been identified as a predictor of clinical outcomes at NSCLC and UC [23], Moreover, several studies bagan to identify gene biomarkers related to NSCLC prognosis [24][25][26]. Another study on AFD involved cervical cancer patients revealed that AFD is positively correlated with therapy response and helps in expecting the progression-free survival 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-house pipelines were used to process the sequencing of 54 WES data. Tumor and normal samples quality data were evaluated using FastQC (http:/www.bioinformatics.babraham.ac.uk/projects/fastqc/), including sequence length distribution, GC content, aspect of per-base quality, sequence duplicate levels, Kemer content and over-represented sequences [27]. Sequencing readings were aligned with the human reference genome (hg38) using the Burrows-Wheeler Aligner (BWA) software package with the default parameters [28], and we removed the reads that were mapped in multiple genome positions.…”
Section: Alignment and Quality Controlmentioning
confidence: 99%